Erzählte Ordnungen - Ordnungen des Erzählens Studien zu Texten vom Mittelalter bis zur Frühen Neuzeit - Fuhrmann, Daniela; Selmayr, Pia (Trends in Medieval Philology, 2021)
By unfurling worlds, narratives also create orders. In addition, their narration has to be structured in an orderly way, so the concept of "order" can be applied to literary texts in two ways: as the order(s) of narration and as narrated order(s).